Charmed ebook - Calonita, Jen (Fairy Tale Reform School, 2016)
The second installment in the beloved Fairy Tale Reform School series where the teachers are (former) villains Sometimes it's good to be bad... It takes a (mostly) reformed thief to catch a spy. Which is why Gilly Cobbler, Enchantasia's most notorious pickpocket, volunteers to stay locked up at Fairy Tale Reform School...indefinitely. Gilly and her friends may have defeated the Evil Queen and become reluctant heroes, but the battle for Enchantasia has just begun. Alva, aka The Wicked One who cursed Sleeping Beauty, has declared war on the Princesses, and she wants the students of Fairy Tale Reform School to join her. As her criminal classmates give in to temptation, Gilly goes undercover as a Royal Lady in Waiting (don't laugh) to unmask a spy...before the mole can hand Alva the keys to the kingdom. Her parents think Gilly the Hero is completely reformed, but sometimes you have to get your hands dirty. Sometimes it's good to be bad... This series is perfect for read-alongs between parents and kids and engaging reluctant readers. Praise for Fairy Tale Reform School: Flunked "Fairy Tale Reform School has a clever concept and a fresh and funny take on the enchanted world. (I always wanted to know what happened to Cinderella's stepmother too!)"—Julia DeVillers, author of the Liberty Porter, First Daughter series and co-author of the Trading Faces series "Spell-binding and wickedly clever."—Leslie Margolis, author of the Annabelle Unleashed novels and the Maggie Brooklyn mysteries